ChemInform Abstract: The Modeling of Biomass Processing. Issue 9 (5th March 2013) - Guo, Na; Caratzoulas, Stavros; Doren, Douglas J.; Sandler, Stanley I.; Vlachos, Dionisios G.
Abstract Review: 72 refs.